Adopting a human rights based approach to international Christian development - Arumugam, Stanley (Koers, 2014)
It is only in the past decade that religion has been recognised as critical to ensuring sustainable international development efforts. This is due in large part to the failure of the dominant development paradigm of Western secularism in the global South. This article focuses on the significant historical contribution of evangelical Christianity in international development and explores some of the ideological tensions that challenge partnership with secular organisations. The resulting separate and parallel efforts of evangelical Christianity and the international non-governmental organisations (INGO) sector are costly and counter-productive in serving the poor. Recently, many INGOs have adopted the human rights-based approach underpinned by its commitment to social justice and solidarity with the poor – values also central to the Bible. It will be argued that this shared approach could provide the necessary bridge to facilitate deeper engagement in the form of social action between secular development actors and evangelicals. The critical role of evangelical Christianity in addressing poverty as a human rights issue in South Africa is also dealt with briefly.